Protective host defense against disseminated candidiasis is impaired in mice expressing human interleukin-37 - van de Veerdonk, Frank L.; Gresnigt, Mark S.; Oosting, Marije; van der Meer, Jos W. M.; Joosten, Leo A. B.; Netea, Mihai G.; Dinarello, Charles A. (Frontiers in Microbiology, 2015)
The effect of the anti-inflammatory cytokine interleukin-37 (IL 37) on host defense against Candida infections remains unknown. We assessed the role of IL 37 in a murine model of disseminated candidiasis using mice transgenic for human IL 37 (hIL 37Tg). Upon exposure to C. albicans pseudohyphae, macrophages from hIL-37Tg mice release 39% less TNFα compared to cells from wild-type mice (P=0.01). In vivo, hIL 37Tg mice displayed a decreased capacity to recruit neutrophils to the site of infection. These defects were associated with increased mortality and organ fungal growth in hIL-37Tg compared to wild-type mice. We conclude that IL-37 interferes with the innate protective anti-Candida host response by reducing the production of proinflammatory cytokines and suppressing neutrophil recruitment in response to Candida, resulting in an increased susceptibility to disseminated candidiasis.